Can geopolitics derail the pandemic treaty? - Ilona Kickbusch; Anna Holzscheiter (The BMJ, 2021)
During the pandemic, the world has experienced how the geopolitics of global health have immediate, ruthless repercussions for the lives and livelihoods of billions, say Ilona Kickbusch and Anna Holzscheiter. The challenge of a pandemic treaty negotiation process is to be responsive to these interconnected levels of geopolitics.
Additional information: The peer review history for this article (including all previous versions of the manuscript, the report from the manuscript committee meeting, the reviewers' comments, and the authors' responses to all the comments from reviewers and editors) is available at https://www.bmj.com/content/375/bmj-2021-069129/peer-review
Keywords: 300